Investigating the effects of emotional maturity and self--discrepancy on the religious attitude of pre-college adolescent girls in Tehran - Ensiyeh Mohammadyari; Anahita Khodabakhshi-Koolaee (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: Achieve to emotional maturity and lack of self-discrepancy is important factors in people's religious attitudes. So the aim this study is Investigating the effects of emotional maturity and self-discrepancy on the religious attitude of pre-college adolescent girls in Tehran Methods: The research method is descriptive and correctional. statistical population consists of all pre-college student girls in Tehran. 405 students were selected using Morgan table and multi-stage cluster sampling method. Data collection tools were emotional maturity questionnaire, self-discrepancy questionnaire and religious attitude questionnaire. Collected data has been analyzed using correlation and regression analysis. All ethical issues were observed. Moreover, the authors did not report conflict of interest. Results: This study Investigated that emotional maturity and self-discrepancy variables determined religious attitudes with a factor of 0.10. The emotional maturity factor (beta-0.31) has the greatest impact on religious attitudes (p<0.01), and real-ideal self-discrepancy with beta 0.11 is the second factor influencing religious attitude in adolescent girls (p<0.05). In this explanation, real-ought self discrepancy had no significant effect on the religious attitude (p>0.05). Conclusion: The results showed that emotional maturity and self-discrepancy variables play important role in the religious attitude of adolescent girls. Therefore these variables must be considered to promote their religion, and field of necessary education to students such as life skills training should be provided to improve emotional maturity and self-discrepancy. For downloading the full-text of this article please click here.